Family Members of Cancer Patients in Korea Are at an Increased Risk of Medically Diagnosed Depression - Youngdae Cho; Yongwoo Jeon; Sung-In Jang; Eun-Cheol Park (Korean Society for Preventive Medicine, 2018)
Objectives Family members are often cancer patients' primary source of social and emotional support and make a major contribution to how well patients manage their illness. We compared the prevalence of depression in the family members of cancer patients and the general population. Methods This study used the data from the fourth, fifth, and sixth rounds of the Korea National Health and Nutrition Examination Survey. The variable of interest was the presence of a cohabitating cancer patient in the family and the dependent variable was the presence of diagnosed depression. Results The odds of having medically diagnosed depression in those with a cohabitating cancer patient in the family were significantly higher than among those who did not have cancer patients in their families (odds ratio [OR], 1.56; 95% confidence interval [CI], 1.12 to 2.17; p=0.009). The OR for females was 1.59, and this increase was statistically significant (95% CI, 1.09 to 2.31; p=0.02). Conclusions We need to invest more effort into diagnosing and managing depression in the family members of cancer patients. This will have an impact both on their quality of life and on the well-being of patients, as supporters and caregivers play an instrumental role in helping patients manage their illness.